In vitro maturation for fertility preservation in patients with cancer: A review - Yulia E. Dobrokhotova; Irina A. Lapina; Anastasiya A. Malakhova; Tatiana G. Chirvon; Vladislav V. Taranov; Yury А. Sorokin; Maria А. Tverdikova; Valeriia M. Gomzikova; Anastasia A. Zateeva; Olesya V. Kaikova (IP Berlin A.V., 2023)
According to the World Health Organization, the number of patients of reproductive age with cancer steadily increases. Therefore, improving their quality of life is one of the priority tasks of the medical community. It is known that more than 30% of women with cancer at the time of diagnosis have not yet given birth. Therefore, one of the relevant issues is developing and improving methods for preserving reproductive function. In vitro oocyte maturation is a promising technique of oncofertility, which is used as an alternative to traditional cycles of ovulation stimulation followed by the production of mature oocytes. This review aims to study the in vitro maturation procedure and analyze the literature data regarding its effectiveness and safety when used as a part of programs for preserving reproductive material in patients with cancer.